Structural and functional analysis of Interleukin-1 F5, a novel member of the Interleukin-1 family - Dunn, Eleanor (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2003)
This study is an investigation into novel members of the Interleukin-1 (IL-1) family; IL-IF5 and IL-1F6. The classical members of the IL-1 family, including IL -1a , IL-1β and IL-18, are involved in immune responses to infection and injury, which they control by activating signalling pathways leading to NFkB and MAP kinase activation. IL-1F5 has highest sequence identity to IL-1 receptor antagonist (IL-1Ra), a natural antagonist of the IL-1 system, with 44% identity at the amino acid level based on structural alignment derived from crystallographic data. IL-1F6, on the other hand, is 30% identical to IL-1R a at the amino acid level. Both proteins are predicted to fold in a manner similar to IL-1 by forming a β-trefoil structure. However, the functions of the proteins are still uncertain. The sequence homology of IL-1F5 to IL1Ra has been used to predict an antagonistic role for this molecule but detailed sequence analysis suggests that it does not have the features that have been shown to determine IL- IRa's antagonistic activity.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin